Analysis of marketing strategies for home industry MSMEs on consumer behaviour - Fitriany, Fitriany (Jurnal Mantik, 2024)
Within the MSME sector, home industries stand out as one of the pillars that drive the local economy. Despite their small scale, home industries have great potential to grow and contribute more to the national economy if managed with the right marketing strategy. Therefore, the main challenge is how MSMEs can convince themselves to adopt digital technology as part of their marketing strategy. Marketing is a key element in business success, including for home industry MSMEs. The purpose of this research analysis is carried out because it departs from one of the main challenges for home industry MSMEs in implementing marketing strategies is limited funds. Therefore, marketing strategies must be designed in such a way as to be effective but still cost-effective or in accordance with the capacity of the business. The research method is qualitative with the design used in this research is a descriptive method with a type of case study. The data collection technique using observation provides direct data from the field and interviews provide insight from the resource person's perspective. The results showed that Fatur Bakery has great potential by utilising strengths and overcoming weaknesses. Market opportunities can be maximised with advanced marketing strategies and improved management. Threats of competition and market changes are anticipated by innovation and rapid adaptation, increasing customer satisfaction and loyalty.